Perbedaan Pengaruh Efektifitas Pemberian Myofascial Release dan Stretching terhadap Penurunan Nyeri pada Neck Pain Non Spesifik - Haryatno, Pajar; Fahri, Ana Mustafiyah; Oktaviani, Vernanda (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Non-specific neck pain is defined as pain in the posterior and lateral aspects of the neck between the superior nuchal line and the first thoracic spinous process without any signs or symptoms of structural pathology. Objectives: To determine which intervention is more effective between myofascial release and stretching in reducing pain in non-specific neck pain. Methods: This study employed a two-group pre-test and post-test design involving 30 respondents who were randomly assigned into two groups. Group I received myofascial release intervention, while Group II received stretching. Both interventions were administered three times per week for two weeks. Pain intensity was measured using the Visual Analogue Scale (VAS) before and after intervention. Data were analyzed using non-parametric tests: the Wilcoxon Signed Rank Test for within-group comparisons and the Mann-Whitney U Test for between-group comparisons. Results: The Wilcoxon test showed significant differences between pre-test and post-test scores in both the myofascial release group (Z = -3.477; p < 0.001) and the stretching group (Z = -3.432; p < 0.001). The Mann-Whitney test indicated no significant difference in pre-test scores between groups (p = 0.839), but a significant difference was found in post-test scores (p = 0.009). Conclusion: Both myofascial release and stretching are effective in reducing pain in non-specific neck pain. However, myofascial release is more effective compared to stretching. Keywords: Pain, Neck Pain, Myofascial Release, Stretching.